2007
DOI: 10.1111/j.1442-9071.2006.01413.x
|View full text |Cite
|
Sign up to set email alerts
|

Progression of retinopathy during pregnancy in type 1 diabetes mellitus

Abstract: Laser photocoagulation for severe NPDR or early PDR prior to pregnancy may protect against rapid progression of PDR. Visual impairment resulting from progression of PDR can be prevented by aggressive laser treatment during pregnancy. Duration of diabetes>15 years, poor glycaemic control and hypertension are high-risk factors in the progression of diabetic retinopathy in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 31 publications
2
66
0
7
Order By: Relevance
“…However, long term detrimental effects are rare 63 64. Laser treatment before pregnancy protects against progression in pregnancy and therefore, wherever possible, should be performed before conception 65. When diabetic retinopathy does develop de novo in pregnancy it is usually not severe and laser treatment is safe if required 65 66.…”
Section: Antenatal Carementioning
confidence: 99%
See 1 more Smart Citation
“…However, long term detrimental effects are rare 63 64. Laser treatment before pregnancy protects against progression in pregnancy and therefore, wherever possible, should be performed before conception 65. When diabetic retinopathy does develop de novo in pregnancy it is usually not severe and laser treatment is safe if required 65 66.…”
Section: Antenatal Carementioning
confidence: 99%
“…Laser treatment before pregnancy protects against progression in pregnancy and therefore, wherever possible, should be performed before conception 65. When diabetic retinopathy does develop de novo in pregnancy it is usually not severe and laser treatment is safe if required 65 66. Good blood pressure and glycaemic control both lessen retinopathy progression 67.…”
Section: Antenatal Carementioning
confidence: 99%
“…Trends toward substantially improved diabetes control during pregnancy are likely to result in lower blood sugar levels and therefore less concern regarding DR risk. Duration of diabetes greater than 15 years, poor glycaemic control and hypertension were identified as high-risk factors in the progression of DR in pregnancy 312 .…”
Section: Pregnancymentioning
confidence: 99%
“…Data were extracted from the abstracts because for the first study we could not get the complete article [12], and for the second study, the article was in the French language but the abstract was in English [13]. Through 45 years (1969Through 45 years ( -2014, most of the studies reported were carried out in Egypt, with 9 studies [14][15][16][17][18][19][20], followed by Saudi Arabia with 5 studies [21][22][23][24][25] (Table 1). The rates of retinopathy among Arab patients with T1D ranged from low in Saudi Arabia [21] to high in Yemen [26] (Table 1).…”
Section: Diabetic Retinopathy In the Arab Countriesmentioning
confidence: 99%